2017
DOI: 10.1108/md-10-2016-0691
|View full text |Cite
|
Sign up to set email alerts
|

Bonding and spreading

Abstract: Purpose: Although social media proficiency and use are key business and marketing practices in today's digital environment, research has failed to offer sufficient insights into what drives small firms to use social media and how they vitalise co-creative social media environments with consumers. In response, we conducted a qualitative research study to examine how small firms utilise social media to interact and build bonds with consumers.These bonds become an important tool in the development of successful, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 73 publications
0
5
0
1
Order By: Relevance
“…They assert that although "stickiness" offers a company an easier way to measure statistics, such as views or visits, it does not reflect the true use of digital media today. Therefore, rather than trying to confine user activity through its website content, a company should encourage open participation and the dissemination of its material across diverse social media platforms (Choi & Burnes, 2017;Green & Jenkins, 2011). When the user relationship and media are both interconnected and networked, digital content can unexpectedly reach large numbers of people.…”
Section: Share (Connectivity Interactivity and Reward)mentioning
confidence: 99%
“…They assert that although "stickiness" offers a company an easier way to measure statistics, such as views or visits, it does not reflect the true use of digital media today. Therefore, rather than trying to confine user activity through its website content, a company should encourage open participation and the dissemination of its material across diverse social media platforms (Choi & Burnes, 2017;Green & Jenkins, 2011). When the user relationship and media are both interconnected and networked, digital content can unexpectedly reach large numbers of people.…”
Section: Share (Connectivity Interactivity and Reward)mentioning
confidence: 99%
“…Hiring a community manager who conducts research on social media and promotes events depending on the participants’ preferences can be a strategic factor in improving the quality of integrated communication between organizations and consumers and in increasing loyalty among attendees (Llopis-Amorós et al 2018 ). Moreover, managers should go beyond adapting their organizations to the changes related to social media platforms and should build solid relationships with their customers, thus increasing the opportunity to achieve greater loyalty and improving their opportunity to involve consumers in the process of co-creation (Choi and Burnes 2017 ).…”
Section: Discussion and Managerial Implicationsmentioning
confidence: 99%
“…This behavior allows Spotify to take over the market demand, reducing its dependency on major labels (Prey et al 2020 ). Choi and Burnes ( 2017 ) studied the impact of using social media in the music industry and confirmed that social media have a considerable impact on fans’ engagement. Therefore, building solid and durable relationships and vitalizing participation should be considered a strategic focus for these firms.…”
Section: Content Analysismentioning
confidence: 94%
“…A despeito do escopo da presente pesquisa, esse aspecto tem validade ampla para o tipo de abordagem aqui realizada. Se é verdade que a música indie vem se tornando tema de discussões promissoras (Choi & Burnes, 2017;Gu, Domer & O'Connor, 2021), isso também vale para tópicos emergentes da indústria do entretenimento, como é o caso de produções realizadas em meio a culturas orientais (e.g., Coreiana, Chinesa, Japonesas), que têm crescido exponencialmente no meio mainstream (Chen, 2021;Matsunobu, 2018;Sugihartati, 2020), Nesse sentido, é válido destacar que o estudo realizado tem como limite e limitação a comunidade virtual observada. É uma limitação por se focar apenas nos fãs de música indie que interagem no fórum investigado, buscando elaborar suas experiências de consumo produtivas através de troca de mensagens com membros desta plataforma.…”
Section: Considerações Finaisunclassified